Penerapan Metode Penghalusan Eksponensial Tunggal pada Prediksi Penjualan Air Minum dalam Kemasan - Dwi Handoko; Andriani Kusumaningrum KW; Retno Tri Vulandari (Jurnal Ilmiah SINUS, 2021)
The Bottled Drinking Water Industry has grown rapidly to various provinces and cities throughout Indonesia now. The development of this industry is caused by high demand from consumers and the lower quality of raw water in springs and wells. PT. Cahaya Bumi Intanpari (CBI) is a company that produces gallons, bottles, and glasses bottled drinking water under the brand “AirMu”. Sales of bottled water every month always fluctuate, the management of PT. Cahaya Bumi Intanpari requires an estimate of the amount of production of each type of bottled water to market demand in the future. Based on the description of the background, in this study, a desktop-based application was designed and built. The research method used includes data collection and data analysis. Data collection includes observation, interviews, and literature study. While data analysis includes making data flow diagrams. The forecasting model is used in forecasting the sales of bottled drinking water at PT. Cahaya Bumi Intanpari is a time series or it can be called a time series, and the forecasting method used is single exponential smoothing. From the results of calculation testing, it is proven that the Single Exponential Smoothing method can be implemented in the AMDK sales forecasting system. Based on the validity test, it is found that the prediction test results of bottled drinking water sales below 20% are included in the good criteria.